Near-infrared time-resolved spectroscopy reveals task-induced emotions by measuring cerebral blood oxygenation changes in the frontal pole during creative activity using a real object - Yumi Oboshi; Kazuki Tamura; Yasuko Fukushi; Seiji Yamamoto (IBRO Neuroscience Reports, 2025)
Creative activities trigger enjoyable feelings, induce motivation, and are applied in clinical settings such as rehabilitation. Emotion and creativity are interrelated because they depend on a common neural network, with the prefrontal cortex playing a crucial role in both. Emotions affect creative thinking, and creative activities elicit emotions. Near-infrared spectroscopy (NIRS) provides a real-time assessment of emotion generated in a natural setting. Furthermore, near-infrared time-resolved spectroscopy (NIR-TRS) can measure brain activity that is less susceptible to extracerebral tissue. We measured oxyhemoglobin (Oxy-Hb) concentrations in the frontal pole, which is involved in emotion processing using NIR-TRS during creative and simple tasks utilizing real objects. Oxy-Hb concentrations in the frontal pole significantly increased during and after the creative task compared with the simple task. The autonomic function indices (heart rate and stress indices) were inversely correlated with the Oxy-Hb increase associated with the creative task performance, indicating that sympathetic nervous system hyperactivity did not cause this Oxy-Hb increase. A subjective survey revealed that positive emotions during the creative activity were significantly higher and correlated well with the increased Oxy-Hb level, indicating an increased frontal pole activity because of the enjoyability of the creative task. Our results indicate that NIR-TRS imaging can be employed for noninvasively measuring cerebral blood oxygenation changes in participants who experience various emotions during creative activities.